2023
DOI: 10.1111/hex.13737
|View full text |Cite
|
Sign up to set email alerts
|

Popular science and education of cosmetic surgery in China: Quality and reliability evaluation of Douyin short videos

Abstract: Background Douyin APP is the short video APP with the largest number of users in China. Objective This study aimed to evaluate the quality and reliability of short videos about cosmetic surgery on Douyin. Methods In August 2022, we retrieved and screened 300 short videos related to cosmetic surgery from Douyin, extracted basic video information, encoded the content and identified the video source. The quality and reliability of short video in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Zhang et al . 26 found that the quality and reliability of the cosmetic surgery videos on Douyin were satisfactory. However, Lan Yao et al .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Zhang et al . 26 found that the quality and reliability of the cosmetic surgery videos on Douyin were satisfactory. However, Lan Yao et al .…”
Section: Discussionmentioning
confidence: 94%
“…TikTok and Douyin, the world's largest short‐video platforms, showed the potential value of health education. Zhang et al 26 . found that the quality and reliability of the cosmetic surgery videos on Douyin were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ranking algorithm of video-sharing platforms not only considers the quality of the videos, but also more considers the likes, comments, reposts, and completion rates. 21 Video content of current platforms is mostly entertainment oriented. However, for medical videos, accuracy and professionalism are more important than entertainment and popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have examined the quality of videos on different themes on TikTok and Bilibili, and there are differences in video quality among different themes. The quality of videos about liver cancer and inflammatory bowel disease is generally unsatisfactory ( 16 , 17 ), but the quality and reliability of videos about plastic surgery are deemed satisfactory ( 18 ). Although breast cancer videos on YouTube and TikTok have been evaluated, we found a large number of videos about breast cancer on TikTok Chinese version and Bilibili, and the information presented has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%